Library Digitalization and Modernization: Strategies for Utilizing E-Clipping to Enhance Services at the Digital Library of the Audit Board of the Republic of Indonesia (BPK RI) Bali Provincial Office - Salsinha, Lucia Maria Dos Santos; Lukman, Juwita Pratiwi (Baileo: Jurnal Sosial Humaniora, 2025)
The rapid development of digital transformation in the 4.0 era has significantly impacted work processes and interactions across various sectors, including library management. The Audit Board of the Republic of Indonesia (BPK RI) Representative Office in Bali Province has adopted a strategic approach by transforming its conventional library into a digital library and implementing e-clipping as a tool to modernize its services. This study aims to evaluate the effectiveness of utilizing e-clipping technology in enhancing the quality of digital library services at BPK RI Bali. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation. The findings indicate that the implementation of e-clipping not only accelerates information access but also improves operational efficiency and user satisfaction. The novelty of this research lies in revealing the integration of e-clipping technology with a digital library system as an innovative model for government institutional libraries in Indonesia. The study concludes by emphasizing the importance of library digitalization as a strategic step toward modernizing technology-based services. It recommends the broader adoption of e-clipping across other government institutions to enhance public service efficiency and contribute significantly to the advancement of social sciences and humanities, particularly in digital information management.